Machine learning model for diagnosing salivary gland adenoid cystic carcinoma based on clinical and ultrasound features - Huan-Zhong Su; Zhi-Yong Li; Long-Cheng Hong; Yu-Hui Wu; Feng Zhang; Zuo-Bing Zhang; Xiao-Dong Zhang (Insights into Imaging)
Abstract Objective To develop and validate machine learning (ML) models for diagnosing salivary gland adenoid cystic carcinoma (ACC) in the salivary glands based on clinical and ultrasound features. Methods A total of 365 patients with ACC or non-ACC of the salivary glands treated at two centers were enrolled in training cohort, internal and external validation cohorts. Synthetic minority oversampling technique was used to address the class imbalance. The least absolute shrinkage and selection operator (LASSO) regression identified optimal features, which were subsequently utilized to construct predictive models employing five ML algorithms. The performance of the models was evaluated across a comprehensive array of learning metrics, prominently the area under the receiver operating characteristic curve (AUC). Results Through LASSO regression analysis, six key features—sex, pain symptoms, number, cystic areas, rat tail sign, and polar vessel—were identified and subsequently utilized to develop five ML models. Among these models, the support vector machine (SVM) model demonstrated superior performance, achieving the highest AUCs of 0.899 and 0.913, accuracy of 90.54% and 91.53%, and F1 scores of 0.774 and 0.783 in both the internal and external validation cohorts, respectively. Decision curve analysis further revealed that the SVM model offered enhanced clinical utility compared to the other models. Conclusions The ML model based on clinical and US features provide an accurate and noninvasive method for distinguishing ACC from non-ACC. Critical relevance statement This machine learning model, constructed based on clinical and ultrasound characteristics, serves as a valuable tool for the identification of salivary gland adenoid cystic carcinoma. Key Points Rat tail sign and polar vessel on US predict adenoid cystic carcinoma (ACC). Machine learning models based on clinical and US features can identify ACC. The support vector machine model performed robustly and accurately. Graphical Abstract